Suppression of the lattice thermal conductivity in NbFeSb-based half-Heusler thermoelectric materials through high entropy effects. (December 2018) - Yan, Jianlong; Liu, Fusheng; Ma, Guohua; Gong, Bo; Zhu, Jiaxu; Wang, Xiao; Ao, Weiqin; Zhang, Chaohua; Li, Yu; Li, Junqin
Abstract: Nb1− x M x FeSb (M = Hf, Zr, Mo, V, Ti; equimolar) thermoelectric materials were prepared by arc melting and subsequent spark plasma sintering. NbFeSb-based half-Heusler phases with a high-entropy lattice were obtained by replacing the Nb sites with multielement M atoms. The lattice thermal conductivity decreased as the M content increased, which mainly resulted from the high entropy effect. A low lattice thermal conductivity of 2.5 W/m K and a high figure of merit of 0.88 were obtained at 873 K, showing the great promise of the high entropy strategy for reducing the lattice thermal conductivity and enhancing the thermoelectric performance. Graphical abstract: Unlabelled Image